Solutions to Increase PV Hosting Capacity and Provision of Services from Flexible Energy Resources - Laaksonen, Hannu; Parthasarathy, Chethan; Hafezi, Hossein; Shafie-khah, Miadreza; Khajeh, Hosna; Hatziargyriou, Nikos (MDPI AG, 2020)
Future smart grids will be more dynamic with many variabilities related to generation, inertia, and topology changes. Therefore, more flexibility in form of several active and reactive power related technical services from different distributed energy resources (DER) will be needed for local (distribution network) and whole system (transmission network) needs. However, traditional distribution network operation and control principles are limiting the Photovoltaic (PV) hosting capacity of LV networks and the DER capability to provide system-wide technical services in certain situations. New active and adaptive control principles are needed in order to overcome these limitations. This paper studies and proposes solutions for adaptive settings and management schemes to increase PV hosting capacity and improve provision of frequency support related services by flexible energy resources. The studies show that unwanted interactions between different DER units and their control functions can be avoided with the proposed adaptive control methods. Simultaneously, also better distribution network PV hosting capacity and flexibility services provision from DER units even during very low load situations can be achieved.
Keywords: distributed energy resources; flexibility services; active network management; frequency control; fi=Sähkötekniikka|en=Electrical Engineering|